Mountain hiking in Tatra National Park - Mokras-Grabowska, Justyna (Turyzm/Tourism, 2016)
Tatra National Park is the most frequently visited national park in Poland. During the peak season (summer), it attracts both ‘fully aware’ tourists, properly prepared for mountain hiking, and ‘casual’ hikers, motivated mainly by the shallow desire to ‘tick off’ the most popular places in the highest Polish mountains. The article describes the specific character of mountain hikers in Tatra National Park during the summer season, with particular attention paid to the motivations and skills involved in active tourism.